2016
DOI: 10.1016/j.tifs.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory potential of mushroom extracts and isolated metabolites

Abstract: Background: In the recent years natural resources are being in focus due to their great potential to be exploited in the discovery/development of novel bioactive compounds and, among them, mushrooms can be highlighted as alternative sources of anti-inflammatory agents. Scope and approach:The present review reports the anti-inflammatory activity of mushroom extracts and of their bioactive metabolites involved in this bioactive action.Additionally the most common assays used to evaluate mushrooms anti-inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 182 publications
1
78
0
2
Order By: Relevance
“…Therefore, the ethanolic extract studied in the present work can be further exploited as a tyrosinase inhibitor to reduce the severity of hyperpigmentation and decrease melanin biosynthesis, partly due to the registered amount on phenolic acids. Regarding the antiinflammatory activity, aqueous, methanolic and ethanolic extracts of G. lucidum presented activity mainly by inhibiting NO, PGE2, TNF-a IL1-b production (Taofiq et al, 2016c). In the present study, ethanolic extract of G. lucidum revealed anti-inflammatory activity by inhibiting NO production.…”
Section: G Lucidum Ethanolic Extracts As Relevant Bioactive Extractssupporting
confidence: 56%
See 2 more Smart Citations
“…Therefore, the ethanolic extract studied in the present work can be further exploited as a tyrosinase inhibitor to reduce the severity of hyperpigmentation and decrease melanin biosynthesis, partly due to the registered amount on phenolic acids. Regarding the antiinflammatory activity, aqueous, methanolic and ethanolic extracts of G. lucidum presented activity mainly by inhibiting NO, PGE2, TNF-a IL1-b production (Taofiq et al, 2016c). In the present study, ethanolic extract of G. lucidum revealed anti-inflammatory activity by inhibiting NO production.…”
Section: G Lucidum Ethanolic Extracts As Relevant Bioactive Extractssupporting
confidence: 56%
“…In the present study, ethanolic extract of G. lucidum revealed anti-inflammatory activity by inhibiting NO production. Even though the phenolic compounds of mushrooms have been identified as the most important contributors to their anti-inflammatory activity (Taofiq et al, 2015), triterpenic acids such as ganoderic acid C1 and lanostane in G. lucidum, have also contributed significantly to its antiinflammatory activity (Taofiq et al, 2016c).…”
Section: G Lucidum Ethanolic Extracts As Relevant Bioactive Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…phenolic compounds, terpenoids, polysaccharides, lectins, steroids, glycoproteins and several lipid components. Several mushroom extracts, as well as their secondary metabolites, have been reported to display important biological functions such as antioxidant, antitumor, antimicrobial, anti-inflammatory, immunomodulator, antiatherogenic, and hypoglycemic activities (Ferreira et al, 2009(Ferreira et al, , 2010Alves et al, 2012;Taofiq et al, 2016). On the contrary, only very few studies have been reported for the antityrosinase, anti-collagenase, anti-elastase and anti-hyaluronidase activities of mushroom extracts and individual compounds (References cited in Tables 1 and 2, respectively).…”
Section: Mushroom Extracts and Individual Compounds As Cosmetic Ingrementioning
confidence: 99%
“…The most famous member of Tricholoma genus is T. matsutake, on which scientist have focused because of its medicinal properties and commercial potential. The various phytochemicals were isolated form the T. matsutake exhibiting anti-inflammatory, antioxidant and anticancer activities (Ding and Hou, 2012;Taofiq et al, 2016;You et al, 2013). Besides this species other Tricholoma species have been also attracted (Chen et al, 2017;Hassan et al, 2015;Sadi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%